Interface Engineering in CuInSe2 Solar Cells Using Ammonium Sulfide Vapors (Solar RRL 7∕2017). Issue 6 (7th June 2017) - Buffière, Marie; Lepetit, Thomas; Khelifi, Samira; El Mel, Abdel‐Aziz
Abstract : Recent progresses in chalcopyrite solar cells have emphasized the importance of the surface engineering of the absorber layer to reach high power conversion efficiencies. Here, Buffiere et al. (article No.201700067 ) report on a novel approach to engineer the surface of Se‐based chalcogenide thin films at room temperature by direct exposure to ammonium sulfide (AS) vapors serving as a sulfur source. When applied to CuInSe2 (CISe) absorbers, the exposure to AS vapors leads to the progressive deoxidation and sulfidization of the surface of CISe thin films. The modification of the surface chemical state results in (i) an improved coverage of the absorber by the chemical bath deposited buffer layer, (ii) a modification of the doping profile of the absorber and (iii) an increase in the open circuit voltage of CISe/CdS/ZnO solar cells. These results are explained according to a possible passivation of Se vacancies by sulfur atoms at the surface of the absorber occurring as a consequence to its exposure to the AS vapors.